Social structuring of the gut microbiome in communally roosting bats - Eleonore Lebeuf-Taylor; Alexandria Cosby; Quinn Webber; Karl Cottenie (PLoS ONE, 2025)
The gut microbiome is the community of microbes that inhabits the gastrointestinal tracts of animals. Laboratory findings have shown that the gut microbiome plays a crucial role in host metabolism, physiology, and immunity. This has led to speculation that selection acts on both host and microbiome—although identifying functionally essential coevolving microbes in wild animals remains challenging. A recent surge of studies in wild populations has identified phylogenetic, spatiotemporal, dietary, and social patterns in host-associated microbiomes. Here, we describe and assess the gut microbiomes of two sympatric bat species: big brown bats (Eptesicus fuscus) and little brown bats (Myotis lucifugus). Although these species share similar diets and environments throughout much of their North American ranges, we found they have distinct gut microbiomes. We find no evidence of a functional core microbiome among big brown bats and identify roost identity as a driver of microbiome composition, likely arising from social transmission among hosts through physical proximity. We conclude that both environmental and social factors drive microbiome composition in big brown bats and that repeated, extensive sampling is required to bring ecological reality to host-associated microbiome studies in wild populations.